Analysis of factors affecting on local government’s financial losses in North Sulawesi - Ompusunggu, Tutur; Karamoy, Herman; Gamaliel, Hendrik (Yayasan Widyantara Nawasena Raharja, 2024)
This study intends to examine if internal control effectivity, audit findings, audit opinion, completion of follow up audit results and characteristics of regional head have impacts on local government’s financial losses. The study will use district and city local governments in North Sulawesi province as a case study to examine this relationship. Using a sample of 80 respondents in the year 2024, this study draws on primary sources to examine all of the local governments in North Sulawesi Province. Multiple linear regression analysis was processed by Smart PLS version 3.0 software program in order to analyze data and evaluate hypothesis. This study demonstrate that: (1) effectiveness of internal control system has a negative and significant effect on local government’s financial losses; (2) audit findings has negative and significant effect on local government’s financial losses; (3) audit opinion has negative and significant effect on local government’s financial losses; (4) completion of follow up audit results has negative and significant effect on local government’s financial losses; and (5) characteristics of regional heads has negative and significant effect on local government’s financial losses.